Pemanfaatan Tembang Anak Madura Sebagai Sarana Pelestarian Bahasa dan Nilai Budaya Di Era Digital - Akmal, A Muzayyanul; Yoharwan Dwi Sudarto; Khusnul Khotimah (Nexus Publishing, 2024)
Indonesia, which is rich in ethnic, cultural, and linguistic diversity, faces significant challenges in preserving its culture amidst the tides of globalization and digitalization. One significant cultural element is children's songs, which serve not only as a source of entertainment but also as an educational tool for teaching cultural values to the younger generation. This research aims to explore the utilization of Madurese children’s songs as a vital cultural heritage in maintaining the preservation of language and cultural values in the face of modern challenges. This study employs a qualitative descriptive research method. Data collection in this research was carried out through observations and interviews. The results of this study indicate that Madurese children’s songs contain moral, social messages, and local wisdom, which help children understand and recognize their cultural identity. Furthermore, the application of digital media and the integration of children's songs into digital platforms are considered effective strategies for maintaining the relevance of local culture. Therefore, this study recommends the need for more integrated efforts to incorporate children's songs into education, leverage social media, and training, to ensure that the values inherent in Madurese children’s songs remain alive and appreciated by future generations.